В. Суриков - Васильева-Шляпина Галина Леонтьевна (Красная площадь, 2003)
Экземпляры: Ф. 4 (20190701) / Инвентарный номер: 46305 / Цена: 150.00 / Сис.шифр: 85.143(2) / Авт.знак: В 19 / ГРНТИ: 18.31.31 / ББК: 85.143(2)